Meta Analisis Pengaruh Penggunaan E-Commerce Terhadap Pemasaran UMKM Kuliner - Vovi Sinta; Pamuji Muhamad Jakak; Primadhy Khema Chandra; Maulaya Arinal Haq (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
With the development of technology, the way people communicate with each other has changed significantly. With the entry of the internet into the business world, marketing strategies have to undergo new changes. As more and more people are connected to the internet, digital marketing is becoming increasingly important. As a result, the purpose of this study is to find out how e-commerce affects the marketing of Culinary MSMEs. This type of research is a qualitative research that uses a literature review method. This method is very suitable and relevant for analyzing the relationship between the use of e-commerce and culinary MSME marketing because it can provide an accurate understanding of current technological advances and find problems and weaknesses in the existing literature. The results of the study show that there is a strong correlation between the research theme and the theme of culinary small and medium enterprises (MSMEs) marketing. Most studies use quantitative data to measure how factors such as social media use, e-marketing combinations, and digital marketing influence purchase intent. Many studies have studied the positive effects of using e-commerce, but few studies have studied the adverse effects or challenges that MSMEs face when adapting to new technologies.